Pengembangan Soal Higher Order Thinking Skills (HOTS) Pada Materi Sumpah Pemuda Dan Jati Diri Keindonesiaan di SMA Pembangunan Laboratorium Universitas Negeri Padang - Nofrialdi Oscar; Ofianto Ofianto (Jurusan Sejarah FIS UNP, 2019)
The problem in this research is thinking ability Higher Order Thinking Skills (Hots) of students who are still low on history subjects. It can be seen from the learning outcomes of students that are still low.Therefore, the researcher wants to develop the matter of history on the learning material